Effect of carbon content on microstructure and mechanical properties of dual phase steels - de la Concepción, Valeria L. (2015)
Dual-Phase steels (DP) are constituted by a ferrite matrix with a martensite fraction, giving a good combination of strength, ductility, capacity of energy absorption and strain hardening. Mechanical properties arecontrolled by martensite and ferrite fractions, martensite carbon content, grain sizes and strength of both phases. The carbon content affects the martensite hardness and the hardenability. This work studied the effect of carbon content on microstructure and mechanical properties of DP steels. Samples of steels with different carbon content were heat treated at different intercritical temperatures, obtaining DP steels with different fractionsof martensite. Microstructural characterization, microhardness and tensile test were made for each condition. Increasing carbon content and martensite fraction hardness and strength were increased. The best properties combination was reach for steels with a carbon content of 0.1 to 0.15% and 50% of martensite.Stress relationships obtained were from 1.55 to 2.25.